ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA DI MASA YANG AKAN DATANG PADA PT.BANK RAKYAT INDONESIA Tbk (Persero) - Pangerapan, Cyndia; Saerang, David; Wokas, Heince (Universitas Sam Ratulangi, 2017)
In predicting the financial condition of banks it need relevant, accurate and reliable financial information and useful for internal and external parties the bank itself and presented in the financial statements. This research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk which is enganged in the banking business. The research obective was to analze the predictive ability of financial ratios in the case ROE, PER and Turnover Total Assets to change in earnings in the future. Data analysis method uses is multiple linear regression analysis with the help of SPSS Software.Keywords:Â ROE, PER, turnover total assets